Optimalisasi Kesiapan Mental Anak Melalui Edukasi dan Permainan Interaktif dalam Mengurangi Kecemasan Pra-Khitan - Tri Budi Santoso; Sri Mulyani; Kanthi Suratih; Anis Laela Megasari; Ika Subekti Wulandari; Erindra Budi (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Mass circumcision often induces anxiety in children, potentially affecting their experience and recovery process. This community service initiative aimed to optimize children's mental preparedness and reduce pre-mass circumcision anxiety through educational and interactive play interventions. The activity took place in Nagwen Village, Klaten Regency, Central Java, involving 41 children aged 7-11 years. The approach employed included interactive educational sessions on the circumcision procedure, its benefits, and strategies for managing discomfort, interspersed with relevant educational games. Additionally, simple relaxation techniques and open question-and-answer sessions were implemented to create a safe and comfortable environment for the children.Observational results indicated an increase in children's understanding of the circumcision process and a significant reduction in anxiety indicators, such as restlessness and repetitive questioning. Children appeared calmer, more cooperative, and enthusiastic, and were able to undergo the circumcision procedure smoothly. Most experienced moderate anxiety with an average score of 6.97, as measured by a self-assessment questionnaire. This program demonstrates that education presented in an enjoyable manner, combined with interactive play, is highly effective in preparing children psychologically for circumcision. The recommendation for this activity is to integrate similar methods into every mass circumcision event to ensure a positive experience and support children's psychological well-being